Applying of the Concept of the Death Penalty in Indonesia and Malaysia - Sahdewa, M Farhas; Nuraeny, Henny; Ma'arif, Rizal Syamsul (Fakultas Hukum Universitas Djuanda, 2025)
The death penalty in the Indonesian Criminal Code is found in Law Number 1 of 1946 (KUHP 1946) and Law Number 1 of 2023 (KUHP 2023). In the 1946 Criminal Code, the legalization of the death penalty is maintained in Article 10 and is positioned as a principal crime, this is different from the 2023 Criminal Code which includes the death penalty in Article 67, then changes the death penalty to a special crime, whereas in Malaysia the legalization of the death penalty is threatened The death penalty in Law 574 is formulated in 2 forms of punishment patterns, namely a single one that places the death penalty as mandatory and alternative. However, in 2023 Malaysia will change the mandatory nature of the death penalty in its state regulations, which are outlined in the Death Penalty Deed 2023 Act 846. In this research the author uses a normative juridical approach, namely a statutory approach; by analyzing the rules and regulations relating to these legal issues. The results of this research are: There are several motives that are most popular in the reasons for using the death penalty in Indonesia, namely that the death penalty has a higher level of effectiveness, has a frightening effect (shock therapy), and is also considered more economical and is used so that no action occurs. the main judge himself (eigenrichting) in society as well and the implementation of the Mandatory Death Law in Malaysia from the perspective of the Common Law System is the same as the hudud law in terms of the same type of jinayah punishment for the convicted perpetrator but is contrary to the hudud punishment in terms of making forgiveness and apology to the Yang diPertuan Agong for violations of hudud, seduction can be carried out if there is ambiguity in the case only.